REPRESENTASI KEPERCAYAAN DALAM PESAN SCAM WHATSAPP BERKEDOK LAYANAN PERBANKAN (AWK TEUN A. VAN DIJK) - Effendi, Darwin; Sulistia, Rika; Aprilia, Winsi; Dina Setiawati, Aisya; Ceca Olivia, Sesilia; Robiah; Riska; Puspita Sari, Rahma; Utami, Faza; Hati, Tiara; Salsabilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines how victims’ trust is established and manipulated in WhatsApp scam messages disguised as banking services, using Van Dijk’s Critical Discourse Analysis (CDA) across the dimensions of text, social cognition, and social context. Data consisting of 16 screenshots of real conversations with scammers impersonating UOB Bank, BCA, and Permata Intan were analyzed qualitatively. Four fraud schemes were identified suspicious credit card transactions, QRIS requests, transaction confirmations, and prize draws constructed through a systematic introduction-body-conclusion structure, specific technical details, assumptions of authority (official logos, customer names), and causal coherence with a threatening tone. The success of the fraud relies on the victim’s mental schema that banks can urgently contact customers via WhatsApp without verification, reinforced by the asymmetrical power relationship between the perpetrator as an institution and the victim as an individual customer. These findings underscore the need for message verification through official channels and the strengthening of the public’s digital security literacy.